An integrative perspective on value creation and capture in buyer-supplier relationships - Minerbo, Claudio (2019)
This research investigates value creation and capture from a buyer-supplier perspective. Previous studies conceptualized several aspects of value in business relationships, including the dimensions of value creation, the processes and manners by which value is created (or cocreated), and value capture as an outcome. Despite that, research has been conducted independently or without much interaction, and it is still unclear how these aspects interact with each other. This study examines the interplay among four components of business relationships: the dimensions of value creation, processes that enable value creation, buyers and suppliers interactions with these processes, and different manners by which value is captured. The research was developed in three phases, each one with specific and complementary objectives, methodology and sample, and resulted in three articles matching each of these phases. Individual and collective contributions of the papers are provided based on an integrative and generalizable framework developed in this study, applicable for both buyers and suppliers. Value is created by means of different dimensions, some of which common to most relationships and others relevant to certain dyads. Different combinations among value dimensions and relationship characteristics may lead to similar outcomes in value capture through price or volume (equifinality), while the value created by collaborative efforts is not captured by the supplier. Individually, each value dimension´s potential to value capture is limited and depend if they are strategically managed as trade-offs or combined. Operational efficiency is a dimension that mostly affects value capture, but is limited to delivering consistent, and not superior performance levels. The benefits of social exchanges is captured indirectly, as it cannot be priced. Methodologically, this study employed methods that have hardly been used to evaluate complex B2B relationships in OM research, such as Qualitative Comparative Analysis (QCA) and Adaptive Choice Based Conjoint experiments (ACBC). From a practical perspective, buyers and suppliers can use the clear, practical and real word framework and insights provided by this study to better understand the different mechanisms and options available to increase the value from their relationships.